Advances in Non-peptidomimetic HIV Protease Inhibitors - Pang, X.; Liu, Z.; Zhai, G. (Current Medicinal Chemistry, 2014)
HIV protease plays a crucial role in the viral life cycle. It can cleave a series of heptamers in the viral Gag and GagPol precursor proteins to generate mature infectious virus particles. Successful inhibition of the protease will prevent this maturation step and hence block the spreading of HIV. However, the rapid emergence of drug resistance makes it urgent to develop new HIV protease inhibitors to combat the global disease. Besides, poor oral bioavailability, unacceptable side effects, high treatment cost and pill burden also trouble the application of HIV protease inhibitors. In such situations, non-peptidomimetic HIV protease inhibitors have drawn an increasing interest as a potential therapeutic option due to their small molecular weight, favorable bioavailability, high stability in vivo, low resistance and cost of production. In this review, we present the recent advances in non-peptidomimetic HIV protease inhibitors. Their design strategies, biological activities, resistance profiles, as well as clinical application will also be discussed.
Keywords: protease inhibitors